2013
DOI: 10.1109/jsac.2013.sup.0513036
|View full text |Cite
|
Sign up to set email alerts
|

Vehicular Communications Using DSRC: Challenges, Enhancements, and Evolution

Abstract: Dedicated Short-Range Communications (DSRC) has been designed to support vehicular communications. In the U.S., DSRC operates in the 5.9 GHz licensed spectrum band. Its physical (PHY) and medium access control (MAC) layers, defined in the IEEE 802.11p standard, are based on the IEEE 802.11 family of Wi-Fi standards. Vehicular communication environments differ significantly from the sparse and low-velocity nomadic use cases of a typical Wi-Fi deployment. Thus, there are many challenges to adapt Wi-Fi technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(16 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Any massively networked IoT based systems will rely on the efficient means of data communications, IAV is the same; different physical layer technologies have been studied for communication of the networked vehicles in close proximity to each other and other roadside units. The technologies studied include Dedicated Short Range Communications (DSRC) and Wireless Access in Vehicular Environments (WAVE) [23]- [25] for intercommunications and ZigBee, Bluetooth for intra communications between the sensors of AVs [26].…”
Section: A Layered Architecture Models For the Iavsmentioning
confidence: 99%
“…Any massively networked IoT based systems will rely on the efficient means of data communications, IAV is the same; different physical layer technologies have been studied for communication of the networked vehicles in close proximity to each other and other roadside units. The technologies studied include Dedicated Short Range Communications (DSRC) and Wireless Access in Vehicular Environments (WAVE) [23]- [25] for intercommunications and ZigBee, Bluetooth for intra communications between the sensors of AVs [26].…”
Section: A Layered Architecture Models For the Iavsmentioning
confidence: 99%
“…This channelization allows the MAC upper layer to perform multi-channel operations [5] and allows safety and other applications to occupy separate channels in order to manage and reduce interference. The four strict SEMs aim to reduce the effect of ICI between these channels although Wu et al have shown that transmitters on adjacent service channels still cause inter-ICI in the safety channel, even when they satisfy the class C requirement [6]. Shaping the 802.11p spectrum in order to reduce leakage and thus ICI is therefore important.…”
Section: 11p Physical Layermentioning
confidence: 99%
“…The plots demonstrate that at higher densities, the performance tends towards an ALOHA-like performance. Adapted from [108] distances. The performance trends towards an ALOHA-like behavior, due to a lack of protection against simultaneous transmissions by nearby nodes.…”
Section: Csma Behavior At High Node Density: Scalability and Fairnessmentioning
confidence: 99%
“…The frame size is assumed to be 300 bytes. Adapted from [108] Last but not least, as highlighted in [13,14] and due to the periodic nature of CAM, most of the VANET traffic will be generated periodically as well: each vehicle will start its broadcast transmissions when switched on and, since then, it will keep the generation of messages with the same initial phase . This means also that if the transmissions by two nodes collide once, they are likely to collide again and again.…”
Section: Csma Behavior At High Node Density: Scalability and Fairnessmentioning
confidence: 99%
See 1 more Smart Citation